Dakwah dan Bisnis Menggabungkan Nilai-Nilai Islam dengan Tujuan Bisnis - Nurseha, Amelia; Pratama, Andika; Setiawan, Sandi; Pandya, M. Hafidz (Universitas Pahlawan Tuanku Tambusai, 2025)
Integration of Islamic values in da'wah and business practices, with a focus on how these two aspects can support each other to achieve the goals of Islam. Da'wah, as a call to the path of Allah, not only serves as a dissemination of spiritual messages but also as a tool to promote business ethics in accordance with sharia principles. Through this approach, business can act as an effective means of da'wah, where business actors apply the values of honesty, trustworthiness, and justice in their transactions. In this context, da'wah forums play an important role in providing business skills training and building networks that support Muslim entrepreneurs. Thus, sharia-based business transformation not only strengthens communities but also contributes to social welfare. This article also highlights the challenges faced in combining da'wah with business practices in the modern era, as well as the opportunities that exist to create a sustainable Islamic business ecosystem.